GENDER INFLUENCE FOR TENSES OF GRAMMAR UNDERSTANDING IN ENGLISH STUDENTS 2018-A OF STKIP PGRI JOMBANG - Nala Sita Rukmi (JURNAL EDUKASI: KAJIAN ILMU PENDIDIKAN, 2019)
Tenses in grammar are considered to be one of the difficult parts of learning English by most young students,because tenses are not well mastered by students as a simple indicator, general students think twelve or maybe sixteen tenses in English. This conceptual confusion leads to a low budget for applying English in the right limits. According to Merriam Webster gender is a person's internal sense of being male, female, some combination of male and female, or neither male nor female. Female and male have different characteristics and different abilities as in understanding grammar. According to Grey (2001) convey that female have the verbal intelligence (language) than male.The type of the research was analytic observational with Microsoft Excel.The study was conducted in English students 2017-B of STKIP PGRI JOMBANG. The population in this study was English students 2017-B of STKIP PGRI JOMBANG. The sample in this study was 10 students that consist 5 male students and 5 female students. The research instrument to collect data was a questioners. The results showed that Gender influences the results of students' understanding of grammar. The factor that most influences the results is the level of student learning. Female is more diligent than male, evidenced by female learning English every day, while male learns English only every month.